Specialized Middle Level Teacher Preparation: Moving From Advocacy to Actualization - Chris M. Cook; Penny B. Howell; Shawn A. Faulkner (Middle Grades Review, 2016)
Is specialized middle level teacher preparation necessary? This essay offers the authors thoughts regarding middle level teaching and the necessity of specialized middle level teacher preparation. The reader is encouraged to further the discussion of middle level teacher preparation from advocacy to actualization.
Keywords: middle grades; teacher preparation; middle school